2020
DOI: 10.1183/13993003.00118-2020
|View full text |Cite
|
Sign up to set email alerts
|

SABRTooth: a randomised controlled feasibility study of stereotactic ablative radiotherapy (SABR) with surgery in patients with peripheral stage I nonsmall cell lung cancer considered to be at higher risk of complications from surgical resection

Abstract: ObjectivesStereotactic Ablative Radiotherapy (SABR) is a well-established treatment for medically inoperable peripheral stage I non-small cell lung cancer (NSCLC). Previous non-randomised evidence supports SABR as an alternative to surgery, but high quality randomised controlled trial (RCT) evidence is lacking. The SABRTooth study aimed to establish whether a UK phase III RCT was feasible.Design and Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…Although a large randomized trial directly comparing SABR with surgery (either lobectomy or limited resection) would be ideal, differences in complication or mortality profiles and patient or physician biases make randomization to invasive vs noninvasive therapies difficult, and planned studies have failed to accrue patients (STARS [NCT00840749], ROSEL [NCT00687986], and ACOSOG [NCT01336894]). A UK feasibility study concluded that a phase 3 trial of surgery vs SABR was not possible due to patient preferences to undergo SABR when presented both options . Nevertheless, 2 studies, STABLE-MATES (NCT02468024) and VALOR (NCT02984761), are ongoing to address this question.…”
mentioning
confidence: 99%
“…Although a large randomized trial directly comparing SABR with surgery (either lobectomy or limited resection) would be ideal, differences in complication or mortality profiles and patient or physician biases make randomization to invasive vs noninvasive therapies difficult, and planned studies have failed to accrue patients (STARS [NCT00840749], ROSEL [NCT00687986], and ACOSOG [NCT01336894]). A UK feasibility study concluded that a phase 3 trial of surgery vs SABR was not possible due to patient preferences to undergo SABR when presented both options . Nevertheless, 2 studies, STABLE-MATES (NCT02468024) and VALOR (NCT02984761), are ongoing to address this question.…”
mentioning
confidence: 99%
“…Eine relevante Limitation bei der Erhebung von randomisierten Daten zum Vergleich der SBRT und der operativen Therapie stellt die mangelnde Rekrutierung aufgrund des Patienten- oder Behandlerwunschs dar (RTOG 1021, STARS: NCT00840749; ROSEL: NCT00687986, SABRTooth [ 3 ]). Nichtsdestotrotz konnten Chang et al.…”
Section: Kommentarunclassified
“…Several attempts to conduct randomized controlled trials (RCT) to directly compare SABR with VATS in treating operable early stage NSCLC patients have been unsuccessful. The UK-based SABRTooth trial, for example, was found to be infeasible, while slow accrual hindered the progress of the STARS and ROESEL trials (12). Despite these challenges, a pooled analysis of the 58 patients recruited from the STARS and ROESEL trials was conducted (13).…”
Section: Introductionmentioning
confidence: 99%